0302 Interactive Associations of Obstructive Sleep Apnea and β-Amyloid Burden among Clinically Normal and Mild Cognitive Impairment Elderly Individuals: An examination of conversion risk. (12th April 2019) - Bubu, Omonigho M; Umasabor-Bubu, Ogie Q; Andrade, Andreia; Chung, Alicia; Parekh, Ankit; Kam, Korey; Mukhtar, Fahad; Seixas, Azizi; Varga, Andrew; Rapoport, David; Ayappa, Indu; Forester, Terrence; et al.
Abstract: Introduction: We determined whether Obstructive Sleep Apnea (OSA) and β-Amyloid Burden (Aβ) act additively or synergistically to promote conversion from cognitive normal (CN) to mild cognitive impairment (MCI) and from MCI to AD. Methods: In this longitudinal observational study, we examined CN (n=298) and MCI (n=418) older adults from the ADNI database (adni.loni.usc.edu). OSA was self-reported during a clinical interview. Brain Aβ was assessed using Florbetapir-PET imaging. The primary outcome of the analysis was conversion from CN to MCI (CN participants) and from MCI to AD (MCI participants). Participants were required to have a baseline and at least one follow-up clinical visit that identified their cognitive status. Logistic mixed-effects models with random intercept and slope were used to assess associations between OSA, Aβ, and risk of conversion from CN to MCI, and MCI to AD. All models included age at baseline, sex, APOE4 status, years of education, and their interactions with time. Results: Of the 716 participants, 329 (46%) were women. The overall mean (SD) age was 74.7 (5.0) years, and the overall mean (SD) follow-up time was 5.5 (1.7) years (Range: 2.7 - 10.9 years). In CN participants at baseline, conversion to MCI was associated with both OSA (β=0.418; 95% CI, 0.133 to 0.703; P<.001) and higher Aβ-burden (β=0.554; 95% CI, 0.215 to 0.892; P<.001). The interaction of OSA and Aβ burden with time was significant (β=1.169, 95% CI, 0.776 to 1.562; P<.001), suggesting a synergistic effect. In MCI participants at baseline, conversion to AD was associated with both OSA (β=0.637; 95% CI, 0.291 to 0.982; P<.001) and higher Aβ-burden (β=1.061; 95% CI, 0.625 to 1.497; P<.001). The interaction of OSA and Aβ burden with time was significant (β=1.312, 95% CI, 0.952 to 1.671; P<.001), suggesting a synergistic effect. Conclusion: In both CN and MCI elderly, Aβ modified the risk of progression to AD in OSA participants. OSA patients maybe more physiologically susceptible as Aβ load becomes increasingly abnormal Support (If Any): NIH/NIA/NHLBI-T32HL129953, RO1AG056031, R01HL118624, K07AG052685